Climate Change Adaptation and Integrated Waste Management in the time of Pandemic in Ondokuz Mayıs University - Yüksel Ardalı; Özge Köksal (Universitas Diponegoro, 2022)
In this study, consumption data for 2020 were obtained from the Administration Activity Reports published annually by Ondokuz Mayıs University (OMU). Waste data were also taken for the 2020 period as the amounts recorded within the scope of the Zero Waste Project carried out by the university. With the collected data, in the second part, the changes in waste types and amounts will be mentioned in addition to the approximate carbon footprint calculation with the effect of the pandemic process experienced with the year 2020, within the scope and limits determined by the university. The amount of waste per person as students and faculty members of the wastes originating from the units of the university was also calculated. By using the amounts of glass, paper, metal and plastic waste types collected separately by the Ministry of Environment and Urbanization, the amount of gains to be obtained against parameters such as energy, raw material use and emission reduction was calculated with the help of zero waste counter. In order to evaluate the zero waste studies carried out by the University. Within the scope of Zero Waste studies of Ondokuz Mayıs University, the types and amounts of waste coming from the units during the 2020 pandemic period were evaluated. Considering the data obtained from the different units of the university, a decrease was observed in the amount of waste, as in the consumption data. In addition to the harmonization of integrated waste management and transfer mechanisms in our university, carbon capture gardens have been designed to be implemented in our university.Keyword: integrated waste management, carbon release, carbon footprint, carbon capture garden